Possibilities for Enhancing the Fruiting in Teak Seed Orchards - Prasad, Ram; Meshram, P. B., Jamaluddin (Indian Forester, 1990)
The insecticide (Monocrotophos), hormones (Alpha Napthyl Acetic Acid) and Rallis tracel-2 (Micronutrient) were used in teak seed orchards at Behrai (Seoni, M.P.). The experiemental results showed that the growth promoting chemical and insecticides are not effective to increase the teak fruit production. Fruit dropping also does not appear to have been affected by these treatments. As the treatment applied within investigation failed to exhibit any positive correlation with the fruit production in teak and thus on older trees (about 10 years) these treatments should not be applied. The insect population can only be reduced to some extent by the treatment with insecticides only if it is beyond the tolerable level.